Economic Polarization and Antisocial Behavior: An Experiment - Maria Bigoni; Stefania Bortolotti; Efşan Nas Özen (Institute of Labor Economics (IZA), 2019)
Economic inequality may fuel frustration, possibly leading to anger and antisocial behavior. We experimentally study a situation where only the rich can reduce inequality while the poor can express their discontent by destroying the wealth of a rich counterpart with whom they had no previous interaction. We test whether the emergence of such forms of antisocial behavior depends only on the level of inequality, or also on the conditions under which inequality occurs. We compare an environment in which the rich can unilaterally reduce inequality with one where generosity makes them vulnerable to exploitation by the poor. We find that the rich are expected to be more generous in the former scenario than in the latter, but in fact this hope is systematically violated. We also observe that the poor engage in forms of antisocial behavior more often when reducing inequality would be safe for the rich. These results cannot be rationalized by inequality aversion alone, while they are in line with recent models that focus on anger as the result of the frustration of expectations.
Keywords: C91; D63; D83; D84; D91; 330; expectations; frustration; inequality aversion; money-burning; punishment